Dillemas of Women’s Career and Family Roles - Reingardienė, Jolanta (Sociologija. Mintis ir veiksmas, 2004)
On the basis of qualitative research, this study analyzes the experiences of women in their career development and the construction of success in their own terms. The particular focus is given to women’s experiences during their childhood socialization (gender differences in identity formation, the quality of parent-child relationship, maternal influence as a positive model of femininity), which is based on the enduring belief that women’s childhood experiences may provide some of the antecedents of successful career achievements. The dilemmas of women’s career and their family roles are the second major focus of this study. They have been revealed by analyzing the effect of family on women’s career development, different strategies to overcome role conflict and to integrate professional and private lives.
Keywords: gender; career; family; role conflict